The Role of Academic Supervision with Coaching Techniques in Developing Pedagogical Competence: A Case Study in Elementary School Teachers - Novi Puspitasari; Tri Murwaningsih; Fadhil Purnama Adi (Universitas Pendidikan Ganesha, 2025)
Teachers’ pedagogical competence remains a challenge in improving the quality of learning in elementary education. Limited reflective practices and insufficient professional support often hinder teachers from developing sustainable instructional strategies.This study aims to analyze the implementation of coaching-based academic supervision in strengthening teachers’ pedagogical competence in primary education. The study employed a qualitative approach with a case study design involving a school principal and fifth-grade teachers who participated in the supervision process. Data were collected through in-depth interviews, participant observation, and document analysis using interview guidelines, observation sheets, and supervision documents as research instruments. The collected data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing. The findings indicate that coaching-based academic supervision is implemented through systematic planning, collaborative supervision, and follow-up actions aimed at strengthening teachers’ pedagogical competence. Despite challenges such as limited time, varying teacher understanding, and institutional support, this supervision approach contributes to improving teachers’ professional development and learning qualityt.